ENHANCING PAIN MANAGEMENT IN ORTHOPEDIC SURGERY: MULTIDISCIPLINARY CARE MODELS INTEGRATING NURSING, PHARMACY, SURGERY AND EMERGENCY MEDICINE - Ali Hamad Ali Al-Salaim, Ali Rubayyi S Alyami, Jameelah Abdulaziz S Almuhsin, Mesfer Mohammed Ali Balhareth, Khalid Abdulrahman Mualla Alharbi, Hadi Mahdi Ali Al Qufayil, Abdulaziz Abdullah Alshehri, Ali Ahmed Almakrami, Musleh Muslim Al-Hujaili,,; Ahmed Mohammed Alshwaikan, (Chelonian Research Foundation, 2022)
Effective pain management following orthopedic surgery is crucial for optimizing patient outcomes and satisfaction. Traditional pain control approaches often rely heavily on opioid medications, which carry risks of adverse effects and potential for misuse. Multidisciplinary care models that integrate the expertise of nursing, pharmacy, surgery, and emergency medicine professionals offer a promising alternativefor enhancing postoperative pain control. These collaborative approaches emphasize multimodal analgesia, patient education, early mobilization, and continuity of care across healthcare settings. By leveraging the unique skills and perspectives of each discipline, multidisciplinary teams can develop individualized pain management plans that minimize opioid use, reduce complications, and improve functional recovery. Successful implementation requires effective communication, shared decisionmaking, and a commitment to evidence-based practices. As healthcare systems seek to address the opioid epidemic and improve surgical outcomes, multidisciplinary pain management represents an important strategy deserving further research and widespread adoption. Keywords: Orthopedic surgery, postoperative pain, multidisciplinary care, multimodal analgesia, opioid reduction, nursing, pharmacy, emergency medicine.